Extended state observer based output feedback control of 2 DoF electro hydraulic servo system - Ashpana Shiralkar; Shailaja Kurode; Bhagyashri Tamhane (Results in Control and Optimization)
Positioning a load in a two-dimensional subspace requires a two-degrees-of-freedom (2 DoF) position control system. The precise positioning of the load has been the driving motivation for electro-hydraulic actuation and its robust control. 2 DoF electro-hydraulic servo system (EHSS) is complex and nonlinear. Each of the 2 DoF is approximated by the second order model with uncertainty. A new sliding variable is proposed for precise finite-time positioning of a load. The extended state observer based controller is devised using higher-order sliding modes. Uncertainties and states are estimated to implement the controller in a finite time. The method is verified in both simulation and experiment. It is shown that the proposed method yield robust and precise positioning of load in two-dimensional subspace.